Programmable all-optical logic gates based on semiconductor optical amplifiers - Sotelo, Félix; Altabás, José Antonio; Cabezón, Miguel; Garcés, Ignacio (Jornada de Jóvenes Investigadores del I3A, 2014)
In this paper, we discuss the feasibility of optical programmable logic devices based on non-linear processing with semiconductor optical amplifiers. We carried out simulations of the architecture of an all-optical 4-bit Look-up Table, which is the basic logic element of larger-scale programmable devices, and experimental results from a proof-of-concept setup using commercially available devices. Experimental work with photonic integrated circuits to assess the feasibility of integration of such architectures is also presented.